Training Program about Energy Efficiency in Existing Buildings: The MARIE Project experience - Correia-da-Silva, José Júlio (2014)
A broad consensus exists on the need to develop new economic models and ways of life based on energy efficiency. To this end, the European Union has adopted a common policy for achieving the ambitious target of an increase of 20% in energy efficiency by 2020. The project MARIE (Mediterranean Building Rethinking for Energy Efficiency Improvement) has emerged as a means for achieving this goal and obtaining an improvement in terms of energy efficiency renovation of existing buildings in the Mediterranean. One of the key challenges of this program is to create a training program common to all Mediterranean countries. Each partner will identify and describe best practices in terms of energy refurbishment of existing buildings or urban areas. Once the data has been collected, an expert team will set up a training program in order to implement best practices across the Mediterranean area. The aim of this paper is to present a profile of the training program as part of the MARIE project and a report on work in progress, with emphasis on the survey of best practices at the regional level, with a view to sharing the knowledge acquired with the scientific and technical community.